UJI TOKSISITAS LIMBAH INDUSTRI BATIK TERHADAP PERUBAHAN MORFOLOGI INSANG IKAN LELE (Clarias sp.) - Nuril Uswatun Khasanah; Riska Andriani; Tita Dewi Fitriani (Prodi Biologi Universitas PGRI Ronggolawe, 2023)
The growth of home-based batik industry in Tuban is rapidly growing, but the waste management is still very simple. Therefore, toxicity tests of the liquid waste generated by the batik industry are needed. This study aims to determine the changes in the morphology of the gills of catfish (Clarias sp.) exposed to toxins in the form of liquid dye waste from the batik industry. This is an experimental study, by adding liquid dye waste from the batik industry with different concentrations in an aquarium containing catfish. Each aquarium consists of five catfish. The concentrations used are 0% (control), 10%, 25%, and 50% for 48 hours. The morphological structure observed is the change in color of the gills of the catfish. The results of the study were analyzed using qualitative descriptive methods. The results showed that there was a difference in the color of the gills of catfish exposed to liquid dye waste from the batik industry. Catfish exposed to liquid dye waste from the batik industry showed gills that were paler and blacker in color, both at concentrations of 10%, 25%, and 50% compared to the control group (concentration 0%) that was not exposed to liquid dye waste from the batik industry.